Development of Wet Noodles Based on Cassava Flour - Akhmad Z. Abidin; Cinantya Devi; A. Adeline (Journal of Engineering and Technological Sciences, 2013)
Cassava is one of Indonesia's original commodities and contains good nutrition and has high productivity and a relatively low price. Cassava flour has a high potential as a substitute for imported wheat flour that is widely used in noodle production. The main purpose of this research was to develop wet noodles from cassava flour that can compete with wet noodles from wheat flour. The research consisted of experiments with several variations of composition and production method for producing cassava flour-based wet noodles. The best result was then examined for its nutritional value, economical value, and market response, and also a comparison was made between the prepared wet noodles and the standard noodles made from wheat flour. The analysis was based on five characteristics: taste, texture, chewiness, aroma, and appearance. Relations between these characteristics with composition, materials used, and methods applied are discussed. The developed cassava flour-based wet noodle meets physical, nutritional, and economical standards. Raw materials of the noodle were cassava flour and a wheat flour composite with a 5:1 ratio, egg, gluten, soda-ash, water, and vegetable oil, while the process was completed in multiple stages. Market response showed that the cassava flour-based wet noodles were 80% similar to wheat-flour noodles.